Efikasi diri sebagai mediator antara insentif, lingkungan kerja, dan pengembangan karir terhadap kepuasan kerja Tenaga Kesehatan Program Nusantara Sehat di Provinsi Kepulauan Riau - Sepyenita, Sepyenita; Ngaliman, Ngaliman; Faizah, Ana (Journal of Management and Digital Business, 2024)
This study aims to analyze the influence of incentives, work environment, and career development on job satisfaction through self-efficacy among healthcare personnel in the Nusantara Sehat Program in the Riau Islands Province. The research employed a quantitative approach, surveying 116 respondents. Data were collected through questionnaires measuring respondents' perceptions of incentives, work environment, career development, self-efficacy, and job satisfaction. Data analysis was conducted using multiple linear regression and path analysis to assess the mediating role of self-efficacy. The results showed that incentives, work environment, career development, and self-efficacy significantly affect job satisfaction. In addition, the work environment and career development affect self-efficacy, while perception is insignificant. Other findings showed that self-efficacy was shown to act as a mediating variable that strengthens the relationship between the work environment and job satisfaction. At the same time, incentives and self-development had no effect. The conclusion of this study emphasizes that increasing incentives, conducive working conditions, and clear career development opportunities can increase job satisfaction in health workers through increasing self-efficacy.